Clarifying the relationship between culture and values and their impact on workplace satisfaction - Heritage, Brody John (Curtin University, 2012)
My research examines the measurement and properties of values and culture, specifically the integration of Finegan's (2000) four factor values model with Cameron and Quinn's (1999, 2006) Competing Values Framework (CVF). The aim of my research was to reduce the blurring between the constructs of values and culture which has led to ambiguities in both measurement and understanding, such that that the measurement of culture has become highly values-centric.Three hundred and twenty nine participants from Australian local government and private healthcare organizations were surveyed using a cross-sectional design with measures based on Cameron & Quinn’s (1999,2006) Organizational Culture Assessment Instrument and Finegan’s (2000) four factor values constructs, as well as measures of job satisfaction, organizational commitment and turnover intention. Examination of the differences and similarities between values predictors and holistic culture predictors with regards to a generalised measure of workplace outcomes (job satisfaction, organizational commitment, turnover intention) was conducted. Methodological comparisons between traditional hierarchical multiple regression analyses and multilevel modelling were conducted as part of this examination, to account for intra-organizational differences in workplace outcomes.Validation of the four factors of culture represented in the Organizational Culture Assessment Instrument (Cameron & Quinn, 1999; 2006) was broadly achieved for both individual and perceived organizational preferences data. Both individual and perceived organizational culture preferences significantly predicted organizational outcomes. Validation of the four factors of values based on Finegan's (2000) constructs was achieved, although solutions for individual preferences and perceived organizational preferences differed. Again, both individual and perceived organizational values preferences predicted organizational outcomes, as expected. Culture preferences, after accounting for values preferences, significantly predicted organizational outcomes for both individual preferences and perceived organizational preferences data. Perceived organizational preferences were considerably more representative of the variability in workplace outcomes in all analyses. Congruence testing using Edwards' (1994) methodology revealed congruence effects between Humanitarian values / Clan culture and Adherence to Convention values / Hierarchy culture preferences, reinforcing Schneider's (1987) Attraction-Selection-Attrition model predictions.While values and culture are entwined in the literature, my results demonstrated that values-centric explanation of organizational outcomes could not explain as much variability in organizational outcomes as a holistic interpretation of culture. As pointed out by Hofstede et al. (1990; 1998) previously, organizational practices add to the explanatory value of organizational culture. Accounting for intra-organizational differences in predicting organizational outcomes was also identified as important. Differences in specified models for values are possibly indicative of perceptual differences of values when applied to the self compared to values applied to the organization, which may warrant different measurement scales depending on how values are being applied. Congruence between Finegan's (2000) values factors and Cameron and Quinn's (1999; 2006) culture factors was noted, but it was not present between all values/factor pairings as originally predicted. A significant proportion of the variability in organizational outcomes could be explained by perceptions of organizational preferences alone. The results of the thesis indicate the importance of the management of employee perceptions of organization culture (including values) for employee wellbeing.